Porównania w Listach z podróży do Ameryki Henryka Sienkiewicza. Analiza lingwistyczna (Conversatoria Linguistica, 2019)
A purpose of this article is to provide linguistic analysis of similes appearing in Henryk Sienkiewicz’s Letters from a Journey to America. The article mainly focused on:•discussing a formal shape of comparative constructions,•classification of similes,•discussing basic subject areas the excerpted similes belong to,•the most important functions of similes in Letters. It was established that the use of comparative constructions was peculiar to the author of Letters from a Journey to America. The frequent collection of similes and the variety of their forms and functions in the column are some examples of the specifity of Sienkiewicz’s style.